A full set of iridium(iv) pyridine-alkoxide stereoisomers: highly geometry-dependent redox properties. Issue 2 (15th November 2016) - Shopov, Dimitar Y.; Rudshteyn, Benjamin; Campos, Jesús; Vinyard, David J.; Batista, Victor S.; Brudvig, Gary W.; Crabtree, Robert H.
Abstract : A complete series of Ir(iv ) diastereomers coordinated with chlorides and bidentate pyridine-alkoxide ligands was prepared, revealing a number of significant unusual properties. Abstract : We introduce and characterize the complete set of possible isomers of Ir IV (pyalk)2 Cl2 (pyalk = 2-(pyridin-2-yl)propan-2-oate), providing valuable insights on the properties of Ir(iv ) species. The pyridine alkoxide ligand strongly stabilizes high oxidation states, essential to accessing the catalytically relevant Ir(iv ) state, and results in robust complexes that can be handled under ambient conditions, even permitting chromatographic separation. The redox properties are isomer-dependent, spanning a 300 mV range, rationalized with ligand-field theory and DFT calculations. The reported complexes exhibit very high kinetic inertness against isomerization, despite highly disparate predicted thermodynamic stabilities, presenting a unique opportunity to study all five possible isomeric complexes with the same ligand set.